Nickel-based catalyst and preparation method and application thereof
By using a nickel-based catalyst composed of an ordered composite porous carbon/molybdenum disulfide material support, a nickel precursor compound and a hydrophobic compound, the preparation of tetrahydrofuran in the prior art has solved the problem of many by-products, difficulty in separation and easy poisoning of the catalyst active center in the preparation of tetrahydrofuran in the prior art. The problem of this is to achieve efficient preparation of high-purity tetrahydrofuran.
Patent Information
- Application Number
- CN202411658128.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
The existing technology for preparing tetrahydrofuran by-products, difficulty in separation, and easy poisoning of catalyst active centers, making it difficult to achieve long-term high-purity production.
The nickel-based catalyst composed of an ordered composite porous carbon/molybdenum disulfide material support, nickel precursor compound and hydrophobic compound is prepared by heat treatment and impregnation to form a high-strength catalyst to ensure the stability of the nickel active center and Selective.
The preparation of bio-based tetrahydrofuran with high purity (≥99.99%) is achieved, which avoids the reduction of catalyst activity and the generation of by-products, and reduces production costs and process complexity.
Smart Images

Figure FDA0005142598440000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical raw material synthesis, and in particular to a nickel-based catalyst and a preparation method and application thereof. Background Art
[0002] Tetrahydrofuran (THF) is an important organic synthesis raw material and solvent, and is widely used in the fields of pharmaceuticals, chemicals, electronics, etc. Common methods for preparing tetrahydrofuran include furfural method, 1,4-butanediol dehydration method and hydrogenation method. Among them, the hydrogenation method is to hydrogenate maleic anhydride, succinic acid and its derivatives to prepare succinic anhydride, tetrahydrofuran, γ-butyrolactone and 1,4-butanediol mixture, and then separate and distill to prepare tetrahydrofuran. The characteristic of this technology is that it can produce succinic anhydride, tetrahydrofuran, γ-butyrolactone and 1,4-butanediol at the same time according to different process conditions. The main disadvantages are that there are many hydrogenation by-products, the separation cost is high, and the maleic anhydride and succinic acid hydrogenation acidic reaction system, generally the acid-resistant system will lead to active center poisoning, and long-term production cannot be carried out. By adjusting the catalytic active center, high-purity tetrahydrofuran without methyltetrahydrofuran can be prepared by directional and highly selective hydrogenation, which has great industrialization potential.
[0003] Hydrogenation catalysts are mainly precious metal catalysts and nickel-based non-metallic catalysts. Among them, precious metal catalysts have high catalytic activity and excellent selectivity, and play an important role in the field of catalytic hydrogenation, but they cannot be used on a large scale due to their high cost. Among non-precious metals, nickel metal has high catalytic activity and selectivity for hydrogen, as well as its low price, and has been widely used in the field of industrial catalytic hydrogenation. The preparation methods of nickel-based catalysts include co-deposition method, reduction method, sol-gel method, volume impregnation method, etc.
[0004] Co-precipitation method: heat the catalyst carrier and dispersant in deionized water, then add nickel compound solution and precipitant, age, filter, wash and dry. The catalyst prepared by this method has high catalytic activity and selectivity, but it is difficult to accurately control the production of active centers. Reduction method: impregnate nickel and phosphorus compounds with the carrier, dry, roast and reduce in hydrogen atmosphere in sequence. This method is simple to prepare industrially, but the preparation temperature is high and the preparation time is long. Sol-gel method: add a solution containing a complexing agent dropwise to an aqueous solution containing nickel, stir to generate a sol, heat to form a gel, bake and grind. The active ingredients in this preparation process are more evenly dispersed, but the preparation cost is high and the preparation cycle is long. Volume impregnation method: impregnate the carrier into an aqueous solution containing nickel compounds, dry and roast in sequence. This method has the advantages of low raw material consumption and low cost.
[0005] Therefore, there is an urgent need to provide a low-cost nickel-based catalyst with high strength and high selectivity. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a nickel-based catalyst and a preparation method and application thereof. The catalyst is composed of an ordered composite porous carbon / molybdenum disulfide material carrier, a nickel precursor compound active component, and a hydrophobic compound component. The purity of the bio-based tetrahydrofuran prepared by the present invention is ≥99.99%.
[0007] The present invention is achieved through the following technical solutions:
[0008] The first object of the present invention is to provide a nickel-based catalyst, wherein the nickel-based catalyst comprises a catalytically active center cluster composed of nickel and a hydrophobic compound; the size of the catalytically active center cluster is: a length of 80nm to 150nm, a width of 30nm to 100nm, and a thickness of 10nm to 30nm;
[0009] The particle strength of the nickel-based catalyst is ≥400N / cm.
[0010] In one embodiment of the present invention, the nickel loading in the nickel-based catalyst is 30 wt% to 60 wt%, and the content of the hydrophobic compound is 0.01 wt% to 0.2 wt%.
[0011] The second object of the present invention is to provide a method for preparing the nickel-based catalyst, comprising the following steps:
[0012] S1, stirring and mixing asphalt and molybdenum disulfide; heat-treating the obtained mixture under oxygen conditions to obtain a porous carbon / molybdenum disulfide material carrier;
[0013] S2, dissolving the nickel precursor compound, the hydrophobic compound and the acid solution in water to obtain a mixed solution;
[0014] S3, impregnating the porous carbon / molybdenum disulfide material carrier obtained in step S1 into the mixed solution obtained in step S2 to obtain a catalyst intermediate;
[0015] S4, subjecting the catalyst intermediate obtained in step S3 to aging, drying and reduction treatment to obtain the nickel-based catalyst.
[0016] In one embodiment of the present invention, in step S1, the mass average molecular weight of the asphalt is 600 to 2000, and the molecular weight distribution is 1.2 to 1.4;
[0017] And / or, the molybdenum disulfide is a nanosheet structure with 5 to 20 layers.
[0018] In one embodiment of the present invention, in step S1, the mass ratio of the asphalt to molybdenum disulfide is 1:5 to 5:1;
[0019] In one embodiment of the present invention, in step S1, the heat treatment conditions are: heat treatment at 200° C. to 400° C. for 3 h to 8 h.
[0020] In one embodiment of the present invention, in step S2, the nickel precursor compound is selected from one or more of nickel chloride, nickel nitrate, nickel sulfate, basic nickel carbonate, nickel acetylacetonate, nickel oxalate, nickel acetate, nickel citrate, nickel hypophosphite, nickel phosphate and nickel formate.
[0021] In one embodiment of the present invention, in step S2, the structural formula of the hydrophobic compound is Where n≥6.
[0022] In one embodiment of the present invention, in step S2, the mass ratio of the nickel precursor compound to the hydrophobic compound is 1-90:0.1-1.
[0023] In one embodiment of the present invention, in step S2, the acid solution is a 1 mol / L to 6 mol / L nitric acid solution.
[0024] In one embodiment of the present invention, in step S4, the aging conditions are: aging at 50°C to 80°C for 12h to 16h;
[0025] And / or, the drying conditions are: 100° C. to 140° C., and the drying time is 10 h to 14 h.
[0026] In one embodiment of the present invention, in step S4, the reduction conditions are: reduction at 160°C to 200°C for 6h to 10h under hydrogen and normal pressure. , This makes the nickel-based catalyst have hydrogenation activity.
[0027] In one embodiment of the present invention, in step S4, the pore volume of the porous carbon / molybdenum disulfide material carrier is 0.2 mL / g to 0.7 mL / g;
[0028] And / or, the particle size of the porous carbon / molybdenum disulfide material carrier is 3 mm to 5 mm;
[0029] And / or, the bulk density of the porous carbon / molybdenum disulfide material carrier is 750 kg / m 3 ~1100kg / m 3 .
[0030] In the nickel-based catalyst of the present invention, nickel exists in the form of atoms and is adsorbed on the carrier by physical adsorption with the hydrophobic compound. The catalytic active center clusters exist in the pores of the carrier, both on the surface and inside.
[0031] The third object of the present invention is to provide the use of the nickel-based catalyst in the preparation of bio-based tetrahydrofuran.
[0032] In one embodiment of the present invention, the purity of the bio-based tetrahydrofuran is ≥99.99%.
[0033] The technical solution of the present invention adopts a high-strength molybdenum disulfide / porous carbon carrier, which can avoid the non-precious metal nickel catalytic center from being lost into the product under pressurized hydrogenation conditions, thereby causing the catalyst activity to gradually decrease, thereby ensuring long-term production; in addition, the hydrophobic compound can make the hydrogenation product quickly desorb from the catalyst surface, and then by adjusting the reaction pressure and temperature, the degree of hydrogenation of the two C=O bonds of succinic acid can be controlled to obtain the target product.
[0034] The porous carbon / molybdenum disulfide carrier of the present invention, due to the layered structural characteristics of molybdenum disulfide, when the carrier is subjected to high temperature treatment, the asphalt will extend along the layered voids, and then undergo dehydration, de-organic matter and other processes at a certain temperature to form a layered carbon structure, which is firmly combined with molybdenum disulfide and produces a large number of pore structures, which is conducive to the dispersion of active metal components. At the same time, this composite carrier structure naturally has a very high mechanical strength, and it is easy to achieve a particle strength of ≥400N / cm, while the particle strength of traditional alumina is difficult to achieve this. The mechanical strength of alumina particles of commercial catalyst carriers can generally reach 100N / cm.
[0035] Compared with the existing technology, it has the following advantages:
[0036] (1) The catalyst used in the present invention has an ultra-high strength of ≥400 N / cm, and the metal is not easily lost during the reaction, which plays a key role in the synthesis of high-purity tetrahydrofuran.
[0037] (2) The catalyst used in the present invention uses porous carbon / molybdenum disulfide as a carrier. The catalyst carrier itself has a certain hydrogenation activity, which can promote the improvement of reaction activity, thereby reducing the reaction temperature, improving the reaction selectivity, and further improving the purity of the product.
[0038] (3) The catalyst used in the present invention uses a hydrophobic compound as an additive, which can make the product tetrahydrofuran desorb from the catalyst surface as quickly as possible, which can not only accelerate the reaction speed, but also avoid further reaction of the product on the catalyst surface, thereby achieving the ultimate goal of achieving polymerization grade product purity. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0040] The present invention provides a nickel-based catalyst. The nickel-based catalyst comprises a catalytically active center cluster composed of nickel and a hydrophobic compound; the size of the catalytically active center cluster is: a length of 80nm to 150nm, a width of 30nm to 100nm, and a thickness of 10nm to 30nm; and the particle strength of the nickel-based catalyst is ≥400N / cm.
[0041] Furthermore, the catalyst is composed of an ordered composite porous carbon / molybdenum disulfide material carrier, a nickel precursor compound active component, and a hydrophobic compound component. The nickel loading in the nickel-based catalyst is 30wt% to 60wt%, and the hydrophobic compound is 0.01wt% to 0.2wt%.
[0042] Furthermore, the porous carbon / molybdenum disulfide carrier is prepared by mixing asphalt and molybdenum disulfide in a mass ratio of 1:1, and heat treating at 200°C to 400°C for 3h to 8h under oxygen conditions, and has a pore volume of 0.2mL / g to 0.7mL / g, a particle size of 3mm to 5mm, and a bulk density of 750kg / m 3 ~1100kg / m 3 The molybdenum disulfide has a nanosheet structure with 5 to 20 layers. In addition, the size of the catalytic active center cluster is: 80 nm to 150 nm in length, about 30 nm to 100 nm in width, and about 10 nm to 30 nm in thickness.
[0043] Furthermore, the nickel precursor compound is one or more of nickel chloride, nickel nitrate, nickel sulfate, basic nickel carbonate, nickel acetylacetonate, nickel oxalate, nickel acetate, nickel citrate, nickel hypophosphite, nickel phosphate, and nickel formate.
[0044] Furthermore, the hydrophobic compound is Where n≥6.
[0045] The present invention also provides a method for preparing the catalyst, comprising the following steps: impregnating the porous carbon / molybdenum disulfide material carrier in a solution of a mixture of a nickel precursor compound and a hydrophobic compound, and then rinsing and drying the porous carbon / molybdenum disulfide structure to obtain a catalyst.
[0046] The particle strength of the nickel-based catalyst is ≥400N / cm.
[0047] The present invention also provides application of the nickel-based catalyst in preparing bio-based tetrahydrofuran.
[0048] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.
[0049] The purity and impurity content of the product were tested by gas chromatography, with a gas chromatography column HP-5 (30m×320μm×0.25μm) and an FID detector. The column temperature conditions were initial temperature 60℃, first-order termination temperature 90℃, heating rate 15℃ / min, and holding for 2min, second-order termination temperature: 230℃, heating rate 10℃ / min, injection port temperature 260℃, split ratio 100:1, injection volume: 0.2μL, hydrogen flow rate: 30mL / min, nitrogen flow rate: 25mL / min. Acetone was used as the solvent to establish the standard curves of bio-based 1,4-succinic acid, tetrahydrofuran, γ-butyrolactone and 1,4-butanediol.
[0050] The strength test of nickel-based catalyst was carried out in accordance with HG / T 2782 standard.
[0051] Example 1
[0052] This embodiment provides a nickel-based catalyst and its application, and the specific steps are as follows:
[0053] (1) asphalt and molybdenum disulfide were stirred and mixed in a mass ratio of 1:1, and heat treated at 300°C for 4 h under oxygen conditions to prepare a porous carbon / molybdenum disulfide carrier with a pore volume of 0.5 mL / g and a particle size of 5 mm;
[0054] (2) weighing 50.00 g of basic nickel carbonate, 159.5 mL (5 mol / L) of dilute nitric acid solution, 0.30 g of sodium dodecyl sulfate, and 500.00 g of deionized water, stirring at 45° C. until all solids are dissolved, to obtain a solution containing a nickel precursor compound;
[0055] (3) The obtained porous carbon / molybdenum disulfide support is impregnated in a solution of a nickel-containing precursor compound, and the mixture is aged at 60° C. for 14 h under stirring, and then dried at 120° C. for 12 h, and reduced under hydrogen conditions at 200° C. for 6 h to obtain a nickel-based catalyst.
[0056] The obtained nickel-based catalyst is used for the hydrogenation reaction of bio-based succinic acid to separate and obtain bio-based tetrahydrofuran with a purity of ≥99.99%.
[0057] Example 2
[0058] This embodiment provides a nickel-based catalyst and its application, which is similar to Embodiment 1, except that:
[0059] In step (2), basic nickel carbonate is replaced with nickel nitrate;
[0060] The obtained nickel-based catalyst is used for the hydrogenation reaction of bio-based succinic acid to separate and obtain bio-based tetrahydrofuran with a purity of ≥99.99%.
[0061] Comparative Example 1
[0062] This comparative example provides a nickel-based catalyst and its application, and the specific steps are as follows:
[0063] (1) asphalt and molybdenum disulfide were stirred and mixed in a mass ratio of 1:1, and heat treated at 300°C for 4 h under oxygen conditions to prepare a porous carbon / molybdenum disulfide carrier with a pore volume of 0.5 mL / g and a particle size of 5 mm;
[0064] (2) Preparation of nickel-based catalyst: Weigh 50.00 g of basic nickel carbonate, 159.5 mL (5 mol / L) of dilute nitric acid solution, and 500.00 g of deionized water and stir at 45° C. until all solids are dissolved to obtain a solution of a nickel-containing precursor compound;
[0065] The obtained porous carbon / molybdenum disulfide support was impregnated in a solution of a nickel-containing precursor compound. The mixture was aged at 60° C. for 14 h under stirring, dried at 120° C. for 12 h, and reduced under hydrogen conditions at 200° C. for 6 h to obtain a nickel-based catalyst.
[0066] The obtained catalyst is used for the hydrogenation reaction of bio-based succinic acid to separate and obtain bio-based tetrahydrofuran with a purity of less than 7%.
[0067] Comparative Example 2
[0068] This comparative example provides a nickel-based catalyst and its application, and the specific steps are as follows:
[0069] (1) Asphalt was heat treated at 300°C for 4 h under oxygen conditions to prepare porous carbon with a pore volume of 0.5 mL / g and a particle size of 5 mm;
[0070] (2) weighing 50.00 g of basic nickel carbonate, 159.5 mL (5 mol / L) of dilute nitric acid solution, 0.30 g of sodium dodecyl sulfate, and 500.00 g of deionized water, stirring at 45° C. until all solids are dissolved, to obtain a solution containing a nickel precursor compound;
[0071] (3) The obtained porous carbon is impregnated in a solution of a nickel-containing precursor compound, and the mixture is aged at 60° C. for 14 h under stirring, and then dried at 120° C. for 12 h, and reduced under hydrogen conditions at 200° C. for 6 h to obtain a nickel-based catalyst.
[0072] The obtained nickel-based catalyst is used for the hydrogenation reaction of bio-based succinic acid to separate and obtain bio-based tetrahydrofuran with a purity of less than 4%.
[0073] Test Case
[0074] The strength of the catalysts prepared in the examples and comparative examples was tested according to the HG / T 2782 standard. The test results are shown in Table 1 below:
[0075] Table 1
[0076] catalyst Strength (N / cm) Example 1 453.8 Example 2 455.2 Example 3 453.8 Example 4 453.8 Comparative Example 1 451.5 Comparative Example 2 200.2
[0077] It can be seen from Table 1 that the strength of the supported catalyst prepared in the example exceeds 450 N / cm. By combining high-strength molybdenum disulfide with porous carbon, the strength of the supported catalyst can be greatly improved.
[0078] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A nickel-based catalyst, characterized in that The nickel-based catalyst comprises a catalytically active center cluster composed of nickel and a hydrophobic compound; the size of the catalytically active center cluster is: 80nm to 150nm in length, 30nm to 100nm in width, and 10nm to 30nm in thickness; The particle strength of the nickel-based catalyst is ≥400N / cm.
2. The nickel-based catalyst according to claim 1, characterized in that The nickel loading in the nickel-based catalyst is 30 wt% to 60 wt%, and the content of the hydrophobic compound is 0.01 wt% to 0.2 wt%.
3. The method for preparing the nickel-based catalyst according to claim 1 or 2, characterized in that: The following steps are involved: S1. Under oxygen conditions, asphalt and molybdenum disulfide are stirred and mixed, and heat treated to obtain a porous carbon / molybdenum disulfide material carrier; S2, dissolving the nickel precursor compound, the hydrophobic compound and the acid solution in water to obtain a mixed solution; S3, impregnating the porous carbon / molybdenum disulfide material carrier obtained in step S1 into the mixed solution obtained in step S2 to obtain a catalyst intermediate; S4, subjecting the catalyst intermediate obtained in step S3 to aging, drying and reduction treatment to obtain the nickel-based catalyst.
4. The preparation method according to claim 3, characterized in that: In step S1, the mass ratio of the asphalt to molybdenum disulfide is 1:5 to 5:
1.
5. The preparation method according to claim 3, characterized in that: In step S1, the heat treatment conditions are: heat treatment at 200°C to 400°C for 3h to 8h.
6. The preparation method according to claim 3, characterized in that: In step S2, the nickel precursor compound is selected from one or more of nickel chloride, nickel nitrate, nickel sulfate, basic nickel carbonate, nickel acetylacetonate, nickel oxalate, nickel acetate, nickel citrate, nickel hypophosphite, nickel phosphate and nickel formate.
7. The preparation method according to claim 3, characterized in that: In step S2, the structural formula of the hydrophobic compound is Where n≥6.
8. The preparation method according to claim 3, characterized in that: In step S2, the mass ratio of the nickel precursor compound to the hydrophobic compound is 1-90:0.1-1.
9. The preparation method according to claim 3, characterized in that: In step S4, the reduction conditions are: reduction at 160° C. to 200° C. for 6 h to 10 h.
10. Use of the nickel-based catalyst according to claim 1 or 2 in the preparation of bio-based tetrahydrofuran.